2020
DOI: 10.1007/s10967-020-07048-1
|View full text |Cite
|
Sign up to set email alerts
|

Using lead isotope ratios to distinguish between samples of diffrent uranium mines

Abstract: In this work, a total of twenty samples selected for investigation originate from South Africa and Namibia uranium mines. The aim of this study was to determine whether the lead ratios measured in particular samples could be used to attribute the uranium sample to the production or reprocessing plant. Measurements were carried out using an inductively coupled plasma mass spectrometer PerkinElmer NexION 2000. The precision obtained for the 208 Pb/ 206 Pb ratio, the 207 Pb/ 206 Pb ratio and the 204 Pb/ 206 Pb ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Twenty-one (55%) blood samples fell within the range measured for all soil samples (excluding Hartbeesfontein), while 17 (45%) fell within the range of Dronfield soil. Three (8%) blood samples fell within the upper limit of water from tailings dams at a South African uranium mine and coal deposits previously reported by Kupi et al (2020) and Díaz-Somoano et al ( 2009), but showed no overlap with those reported for tailing dams of uranium mined in Namibia (Fig. 3).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Twenty-one (55%) blood samples fell within the range measured for all soil samples (excluding Hartbeesfontein), while 17 (45%) fell within the range of Dronfield soil. Three (8%) blood samples fell within the upper limit of water from tailings dams at a South African uranium mine and coal deposits previously reported by Kupi et al (2020) and Díaz-Somoano et al ( 2009), but showed no overlap with those reported for tailing dams of uranium mined in Namibia (Fig. 3).…”
Section: Resultssupporting
confidence: 57%
“…3). The limited overlap between vulture blood isotopic ratios and those reported by Kupi et al (2020) for water from tailings dams at uranium mines in South Africa, suggests that these mining activities cannot significantly contribute to lead poisoning in Dronfield chicks; a conclusion that is supported by the limited occurrence of white-backed vultures within the Witwatersrand basin (Fig. 1).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations